Development of measures to evaluate youth advocacy for obesity prevention. Issue 1 (December 2016) - Millstein, Rachel; Woodruff, Susan; Linton, Leslie; Edwards, Christine; Sallis, James
Abstract Background Youth advocacy has been successfully used in substance use prevention but is a novel strategy in obesity prevention. As a precondition for building an evidence base for youth advocacy for obesity prevention, the present study aimed to develop and evaluate measures of youth advocacy mediator, process, and outcome variables. Methods The Youth Engagement and Action for Health (YEAH!) program (San Diego County, CA) engaged youth and adult group leaders in advocacy for school and neighborhood improvements to nutrition and physical activity environments. Based on a model of youth advocacy, scales were developed to assess mediators, intervention processes, and proximal outcomes of youth advocacy for obesity prevention. Youth (baselinen  = 136) and adult group leaders (baselinen  = 47) completed surveys before and after advocacy projects. With baseline data, we created youth advocacy and adult leadership subscales using confirmatory factor analysis (CFA) and described their psychometric properties. Results Youth came from 21 groups, were ages 9–22, and most were female. Most youth were non-White, and the largest ethnic group was Hispanic/Latino (35.6 %). The proposed factor structure held for most (14/20 youth and 1/2 adult) subscales. Modifications were necessary for 6 of the originally proposed 20 youth and 1 of the 2 adult multi-item subscales, which involved splitting larger subscales into two components and dropping low-performing items. Conclusions Internally consistent scales to assess mediators, intervention processes, and proximal outcomes of youth advocacy for obesity prevention were developed. The resulting scales can be used in future studies to evaluate youth advocacy programs.